Evaluation of Topical Capislow Extract and Long Pulsed Nd-YAG Laser in the Treatment of Idiopathic Hirsutism - Shokeir, Hisham; Samy, Nevien; Mahmoud, Hend; Elsaie, Mohamed (Journal of Lasers in Medical Sciences, 2018)
Introduction: Hirsutism is a condition that affects 10% of women worldwide. In many cultures, hirsutism is regarded as loss of femininity and can be psychologically traumatizing to the suffering females. The aim of the present study was to evaluate how topical capislow would affect or enhance the efficacy of laser hair removal. Methods: A randomized, monoblinded, placebo controlled split face study of combined topical capislow and long pulsed Nd-YAG laser on one side of the face versus long pulsed Nd-YAG laser alone on the opposite side of the face. Laser sessions were done at 4 weeks interval for maximum seven sessions. Topical capislow and placebo were applied once daily from the day of the first laser session to the day of the last laser session. Patients were evaluated both subjectively and objectively in each laser session and for six months after the last laser session. Results: Both treatment modalities were well tolerated and accepted with significantly better results in combined capislow and laser group versus laser alone. Conclusion: Topical capislow can represent a safe and effective synergistic method for laser with faster results but this is a temporary effect retained only to the time of its application.